Investment Decisions among Homemakers: The Influence of Financial Technology, Income, and Financial Literacy - Haryono, (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Homemakers play a crucial role in family financial decision-making, but the literature on the factors influencing their investment behavior is limited. This study aims to conduct a systematic review of the existing literature on the impact of financial technology, income level, and financial literacy on the investment decisions made by homemakers.The literature review was conducted by searching for relevant scientific articles through online databases such as Google Scholar, Scopus, and Web of Science. Articles that met the inclusion and exclusion criteria were qualitatively analyzed. Based on the literature review, financial technology, income level, and financial literacy were found to be critical factors influencing investment decisions among homemakers. The advancement of financial technology (fintech) has increased the accessibility and participation of homemakers in investing. Higher income levels provide homemakers with more adequate financial resources to invest. Good financial literacy enables homemakers to make more informed and profitable investment decisions. The findings of this literature review underscore the importance of financial technology, income, and financial literacy in driving investment participation among homemakers. These insights can serve as a foundation for future empirical research and have significant implications for academics, regulators, and financial industry practitioners in developing strategies to enhance financial inclusion and household financial well-being.